I am not Joey Pigza / 4. - Gantos, Jack (Farrar, Straus and Giroux, 2007)
Joey's father returns, calling himself Charles Heinz and apologizing for his past bad behavior, and he swears that once Joey and his mother change their names and help him fix up the old diner he has bought, their lives will change for the better.